A study on awareness level on occupational safety and health on employees of Jabatan Air Negeri Sabah and Sabah Electricity Sdn Bhd / Anis Ismail and Ain Azreen Azahr - Ismail, Anis; Azahr, Ain Azreen (Faculty of Business and Management, 2014)
Occupational safety and health is one of the issues that has begin to reach people’s attention. A report by Social Security Organization (SOCSO) stated that the number of accidents in year 2012 has risen to 61,552 accidents, compare to 59,897 accidents in the year 2011. Both Jabatan Air Negeri Sabah and Sabah Electricity Sdn Bhd are in the same utilities sector. Utilities sector employees are more exposed to hazard at work place such as machinery usage, current exposure, and chemical substances. Thus, this study was done to study the employees awareness level on occupational safety and health. The study has been conducted at Jabatan Air Negeri Sabah and Sabah Electricity Sdn Bhd, involving 80 respondents in different departments. Result of the study shows that the most influential factors of employee awareness level on occupational safety and health is employee commitment. Recommendations for future research were also discussed by the researchers in this report.